A dense cluster of D1+ cells in the mouse nucleus accumbens. Issue 1 (10th November 2016) - Petryszyn, Sarah; Sánchez, Maria Gabriela; Gagnon, Dave; Beaulieu, Jean‐Martin; Parent, André; Parent, Martin
Abstract: The striatum is known to be largely composed of intermingled medium‐sized projection neurons expressing either the D1 or the D2 dopamine receptors. In the present study, we took advantage of the double BAC Drd1a‐TdTomato/Drd2‐GFP (D1 /D2 ) transgenic mice to reveal the presence of a peculiar cluster of densely‐packed D1 + cells located in the shell compartment of the nucleus accumbens. This spherical cluster has a diameter of 110 µm and is exclusively composed by D1 + cells, which are all immunoreactive for the neuronal nuclear marker (NeuN). However, in contrast to other D1 + or D2 + striatal cells, those that form the accumbens cluster are devoid of calbindin (CB) and DARPP‐32, two faithful markers for striatal projection neurons. Using GAD‐GFP transgenic mice, we confirm the GABAergic nature of the D1 + clustered neurons. Intracellular injections from fixed brain slices indicate that these neurons are endowed with distinctive morphological features, including a small (5–6 µm), round cell body giving rise to a single primary dendrite that branches into two secondary processes. Single‐neuronal injections combined to electron microscopy reveal the existence of GAP junctions linking these D1 + cells. Based on their location, morphological characteristics and neurochemical phenotype, we conclude that the D1 + accumbens cluster form a highly compact group of small neurons distinct from the larger and more diffusely distributed D1 + or D2 + striatal projection neurons that surround it. This remarkable nucleus might play a crucial role in the limbic function of the murine striatum. Abstract : The use of double BAC transgenic mice has allowed us to discover a peculiar cluster of densely‐packed D1 + cells located in the shell compartment of the murine nucleus accumbens. This spherical cluster was found to be exclusively composed of mature GABAergic D1 + neurons that are devoid of calbindin and DARPP‐32, and intimately linked together through GAP junctions.